1974
DOI: 10.1002/chin.197413047
|View full text |Cite
|
Sign up to set email alerts
|

ChemInform Abstract: THE STUDY OF HETEROGENEOUS PROCESSES BY THERMAL ANALYSIS

Abstract: In der umfassenden Übersicht werden heterogene Gleichgewichte, ihre Untersuchung durch thermische Analysenmethoden, die Theorie der Kinetik und des Mechanismus nichLkatalytischer heterogener Prozesse, die Kinetik bei nichtisothermen Bedingungen sowie die für die thermische Analyse notwendige Apparatetechnik behandelt.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
28
0

Year Published

1976
1976
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(28 citation statements)
references
References 1 publication
0
28
0
Order By: Relevance
“…Several equations [17][18][19][20][21][22] have been proposed as means of analyzing a TG curve and obtaining values for kinetic parameters. Many authors [17][18][19][20][21] have discussed the advantages of this method over the conventional isothermal method. The rate of a decomposition process can be described as the product of two separate functions of temperature and conversion [18], using…”
Section: Kinetic Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Several equations [17][18][19][20][21][22] have been proposed as means of analyzing a TG curve and obtaining values for kinetic parameters. Many authors [17][18][19][20][21] have discussed the advantages of this method over the conventional isothermal method. The rate of a decomposition process can be described as the product of two separate functions of temperature and conversion [18], using…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…Many authors [17][18][19][20][21] have discussed the advantages of this method over the conventional isothermal method. The rate of a decomposition process can be described as the product of two separate functions of temperature and conversion [18], using…”
Section: Kinetic Studiesmentioning
confidence: 99%
“…5. The reduction peaks at higher temperatures (above 450 o C) indicated that the Pt was well interacted with the support in the presence of Sn [5,6,14,34]. The peak height and width increases with the increase in Sn loading, between 400 to 600 o C that may be due to joint reduction and valuable interaction between Pt and Sn on the SAPO-34 [24].…”
Section: Wwwintechopencommentioning
confidence: 99%
“…Several equations [42][43][44][45][46][47][48][49] have been proposed as means of analyzing a TG curve and obtaining values for kinetic parameters. Many authors [42][43][44][45][46] have discussed the advantages of this method over the conventional isothermal method.…”
Section: Kinetic Studiesmentioning
confidence: 99%